НІМЕЦЬКЕ НАСЕЛЕННЯ ПІВДНЯ УКРАЇНИ: ІСТОРІОГРАФІЯ ПИТАННЯ ЗА ПУБЛІКАЦІЯМИ 20-х рр. ХХ ст. (Zaporizhzhia Historical Review, 2021)
The following article presents the analysis of the historical and politological literature of the 1920ís which studies the Ukrainian-German relations. It deals with the problems of the participation of German population in the peasantís revolts of the South Ukraine and Brest-Lithuania peace treaty